2022
DOI: 10.1039/d2ob00890d
|View full text |Cite
|
Sign up to set email alerts
|

Non-covalent interactions in the glutathione peroxidase active center and their influence on the enzyme activity

Abstract: In this computational work, the structure of the active centre of the enzyme glutathione peroxidase (in three forms –SeH, –SeOH and –Se(O)OH) and the non-covalent interactions in it were investigated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…Synergistic strengthening of the halogen bond through formation of an additional hydrogen bond has been shown on the example of an enzyme of the hydrolase class, T4 lysozyme, where original tyrosine residue was replaced by chlorotyrosine 35,36 . In our recent work it was demonstrated that formation of weak but numerous non‐covalent interactions in the active site of glutathione peroxidase enzyme drive the reaction of peroxide reduction 37 . Furthermore, there have been several demonstrations of successful practical use of mutual influence of numerous non‐covalent interactions.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Synergistic strengthening of the halogen bond through formation of an additional hydrogen bond has been shown on the example of an enzyme of the hydrolase class, T4 lysozyme, where original tyrosine residue was replaced by chlorotyrosine 35,36 . In our recent work it was demonstrated that formation of weak but numerous non‐covalent interactions in the active site of glutathione peroxidase enzyme drive the reaction of peroxide reduction 37 . Furthermore, there have been several demonstrations of successful practical use of mutual influence of numerous non‐covalent interactions.…”
Section: Introductionmentioning
confidence: 90%
“…35,36 In our recent work it was demonstrated that formation of weak but numerous non-covalent interactions in the active site of glutathione peroxidase enzyme drive the reaction of peroxide reduction. 37 Furthermore, there have been several demonstrations of successful practical use of mutual influence of numerous non-covalent interactions. For instance, formation of additional hydrogen bonds between substrate and chiral template was used as a tool to control the enantioselectivity of reactions.…”
mentioning
confidence: 99%
“…However, the contribution of the induction and dispersion components is also relatively large and unneglectable. The sum of these two components accounts for about 38 1 for all of the investigated complexes.…”
Section: Sapt Analysismentioning
confidence: 99%
“…10,11 Prompted by these considerations, considerable effort has been made to ascertain the mechanisms of action and modes of supramolecular association with biologically-relevant substrates. 12–21 Over and above biological roles/applications, selenium compounds attract interest in terms of the sensing of anions and molecules, 22–24 and, increasingly, catalysis, 25–28 materials, 29–31 covalent organic frameworks (COFs) 32,33 and as fluorescence probes 34 – all again demanding investigations of the supramolecular chemistry of selenium. Complementing these specialist reviews are more general overviews of the broader roles and implications of chalcogen-bonding.…”
Section: Introductionmentioning
confidence: 99%